2-(Halogenated Phenyl) acetamides and propanamides as potent TRPV1 antagonists. (15th September 2021) - Kang, Jin Mi; Kwon, Sun Ok; Ann, Jihyae; Lee, Sunho; Kim, Changhoon; Do, Nayeon; Jeong, Jin Ju; Blumberg, Peter M.; Ha, Heejin; Vu, Thi Ngoc Lan; Yoon, Sanghee; Choi, Sun; et al.
Graphical abstract: Abstract: A series consisting of 117 2-(halogenated phenyl) acetamide and propanamide analogs were investigated as TRPV1 antagonists. The structure–activity analysis targeting their three pharmacophoric regions indicated that halogenated phenyl A-region analogs exhibited a broad functional profile ranging from agonism to antagonism. Among the compounds, antagonists 28 and 92 exhibited potent antagonism toward capsaicin for h TRPV1 with Ki[CAP]  = 2.6 and 6.9 nM, respectively. Further, antagonist 92 displayed promising analgesic activity in vivo in both phases of the formalin mouse pain model. A molecular modeling study of 92 indicated that the two fluoro groups in the A-region made hydrophobic interactions with the receptor.